2004
DOI: 10.1021/ma0354492
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polythiophene Derivatives Bearing Ferroelectric Liquid Crystalline Substituents

Abstract: A chiral liquid crystalline (LC) substituent with a fluorine-containing asymmetric moiety was introduced into the 3-position of a thiophene ring. Polymerizations of 2,5-dibrominated thiophene derivatives were carried out through dehalogenative polycondensations. Polythiophene derivatives thus prepared were fusible and soluble in ordinary organic solvents. An absorption band was observed in the range of 400−415 nm. Phase transition behaviors of the polymers and monomers were examined by differential scanning ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…[59][60][61][62][63][64] The chemical structures are shown in Chart 21. Ferroelectricity is required to have a spontaneous polarization that is generated by assembly of dipole moments.…”
Section: Side-chain Lc Conjugated Polymersmentioning
confidence: 99%
“…[59][60][61][62][63][64] The chemical structures are shown in Chart 21. Ferroelectricity is required to have a spontaneous polarization that is generated by assembly of dipole moments.…”
Section: Side-chain Lc Conjugated Polymersmentioning
confidence: 99%
“…Recently, a variety of polythiophenes containing liquidcrystalline cores and light-emitting chromophores have been prepared. [50,57,[110][111][112][113] Previously, we have synthesized a series of polythiophene derivatives with the mesogenic units directly attached to the main chain without spacers and found that no spacers between the bulky mesogenic pendant and the polythiophene backbone results in the loss of liquid-crystallinity. [114] Thus, Chen and co-workers have designed and synthesized a series of thiophene and polythiophene derivatives with flexible spacers by introducing terphenyl-containing mesogens into the 3-position of the thiophene (Scheme 5).…”
Section: Polythiophenes (Pts)mentioning
confidence: 99%
“…[47] Attracted by both fundamental and practical points of view, recently, a variety of LCCPs based on different conjugated main chains have been synthesized, such as polyacetylenes, polythiophenes and polyphenylenes, which can be endowed with such functional properties as mesomorphism, luminescence, photoconductivity, gas permeability, chain helicity. [48][49][50][51][52][53][54][55][56][57][58][59] Liquid crystals and light emitting are complementary in property; a polymer with the two electrooptical features (both liquid-crystalline and light-emitting) is of practical value, which may offer very high carrier mobility and emit polarized light [60] and become a promising candidate for novel electronic and photonic devices. The terphenyl is not only a light-emitting chromophore but also a mesogenic core.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The first class of materials takes advantage of the block copolymer's ability for phase separation into well-ordered morphologies (spherical, cylindrical or lamellar) to form separate conduction pathways for charge carriers, thanks to the antagonistic chemical nature of each block at the origin of the nanosegregation. [24][25][26][27] However, the optimal charge transport properties also require the formation of long-range correlated structures with an orientational control of regular pathway alternation.…”
Section: Introductionmentioning
confidence: 99%